Bone mineral density in elite 7- to 9-yr-old female gymnasts and swimmers - Cassell, C.; Benedict, M.; Specker, B. (Medicine & Science in Sports & Exercise, 1996)
It is has been suggested that physical activity may increase bone mineral density (BMD) in children, thereby preventing development of osteoporosis later in life. We studied 14 gymnasts, 14 swimmers, and 17 controls to investigate whether participation in different types of sports among girls 7-9 yr of age is associated with higher total body BMD. Gymnasts were lighter than both swimmers and controls (P = 0.001), and a larger percent of gymnasts compared with swimmers and controls were below the 25th percentile for height and weight. Fat mass, percent body fat, and lean mass were less in gymnasts compared with swimmers and controls (all P < or = 0.05). The relationship between total body BMD and body weight differed among the three groups (interaction term of weight and sport, P < 0.001); the increase in BMD per unit increase in body weight was more among gymnasts than among swimmers and controls. These results indicate that high impact bone loading activities may lead to increased bone density among young girls.